Hearing loss, cleft palate, and congenital hip dysplasia in female carriers of an intragenic deletion of AMMECR1. Issue 5 (27th January 2022) - Koene, Saskia; Knijnenburg, Jeroen; Hoffer, Mariette J. V.; Zwanenburg, Fleur; Haak, Monique C.; Locher, Heiko; van Beelen, Edward S. A.; Santen, Gijs W. E.; Rotteveel, Liselotte J. C.
Abstract: Previously, mutations in the AMMECR1 gene have been described in six males with developmental delay, sensorineural hearing loss (SNHL) and/or congenital abnormalities, including fetal nuchal edema, fetal pericardial effusion, talipes, congenital hip dysplasia, elliptocytosis and cleft palate. In this report, we present three female relatives of a male fetus with an intragenic deletion in this X‐linked gene. All three women reported hearing loss and one was born with a soft cleft palate and hip dysplasia. The audiograms showed mild to moderate SNHL with a variable pattern of the affected frequencies. Immunohistochemical analysis of fetal cochlea was performed confirming the expression of AMMECR1 in the human inner ear. Since hearing loss, cleft palate and congenital hip dysplasia were reported before in male AMMECR1 point mutation carriers and AMMECR1 is expressed in fetal inner ear, we suggest that female carriers may display a partial phenotype in this X‐linked condition.